PENGARUH TEKNIK RELAKSASI GUIDED IMAGINARY TERHADAP INTENSITAS NYERI PADA PASIEN POST OPERASI LAPARATOMY DI RS DR. MOEWARDI SURAKARTA - Rosida, Yuntafiur; , STIKES PKU Muhammadiyah Surakarta, & Yuli Widyastuti (Jurnal Kebidanan, 2014)
ABSTRACT Hospital Dr. Moewardi there are many patient who underwent surgery. Surgery or surgery is often performed during the months of August to November 2012 include 158 fracture (40%) cases, laparatomy 230 (60%) cases. Based on the data in the above case is the most dominating laparatomy.Surgery has the effect of post operative pain after. Based on the interviews with one of the nurses said that, when patients experience post operative pain laparatomy especially the nurses analgesics to relieve pain. In addition to pain management nurses use deep breathing relaxation techniques if the patien did not receive analgesic therapy. Nurses rarely apply relaxation techniques guided imaginary because they think the application of deep breathing relaxation techniques simpler. To determine the influence of imaginary guided relaxation techniques to decreasethe intensity of pain in post operative laparatomy patient in hospital Dr. Moewardi. The design used in this research is one pretest-posttest design. The population used in this study were patients post surgery in the Rose II RS Dr. Moewardi. The sampling technique used was purposive sampling. Number of samples 16 respondents. The instrument used for examination of pain using a pain scale gauge Bourbanis.Data processed by computer SPSS Version 16.00 value effectÂ SPSS Version 16.00 value effect p = 0.000 < 0.05 at 95% significance. Comparison of the pretest (mean = 5.88) and posttest (mean = 3.56), the average pain score of patients after administration of imaginary is guided 2.32 indicates that there are between teknk guided imaginary influence on the reduction of pain intensity score (p = 0,000 <0,05) at 95%Â significance. There is a guided relaxation techniques imaginary influence the intensity of pain in postoperative laparotomy patients in hospital Dr. Moewardi. Keywords: Laparotomy, pain, guided imaginary